2019
DOI: 10.1158/2159-8290.cd-18-0193
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the Collagen Matrix in Aging Skin Promotes Melanoma Metastasis and Affects Immune Cell Motility

Abstract: Physical changes in skin are among the most visible signs of aging. We found that young dermal fibroblasts secrete high levels of extracellular matrix (ECM) constituents, including proteoglycans, glycoproteins and cartilage-linking proteins. The most abundantly secreted was HAPLN1, a hyaluronic and proteoglycan link protein. HAPLN1 was lost in aged fibroblasts, resulting in a more aligned ECM that promoted metastasis of melanoma cells. Reconstituting HAPLN1 inhibited metastasis in an aged microenvironment, in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
274
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 296 publications
(285 citation statements)
references
References 62 publications
8
274
2
1
Order By: Relevance
“…We here identify an enrichment of ECM organization and trafficking genes within our MetDev cohort, consistent with a known role for these in metastasis [62][63][64] . Further analysis of these genes/pathways may prove a rich resource to uncover novel metastasis biology.…”
Section: Discussionsupporting
confidence: 84%
“…We here identify an enrichment of ECM organization and trafficking genes within our MetDev cohort, consistent with a known role for these in metastasis [62][63][64] . Further analysis of these genes/pathways may prove a rich resource to uncover novel metastasis biology.…”
Section: Discussionsupporting
confidence: 84%
“…In human lung and ovarian tumors we found that T cells preferentially accumulate and migrate in stromal regions that exhibited a loose matrix architecture but not in dense regions (11,38). Likewise, in aged skin, dermal fibroblasts harbor a phenotype similar to CAFs and produce ECM matrices that limit T cell displacements (43). However, in triple-negative breast cancers and in pancreatic tumors T cells were still found in dense networks of collagen fibers (35,44).…”
Section: Discussionmentioning
confidence: 86%
“…However, in cancer, disruption of BMs is commonly observed. A series of recent studies (40,41) demonstrated that the ECM molecule hyaluronan and proteoglycan link protein-1 (HAPLN1) decreased with aging of the ECM. This resulted in disruption of the vascular BM and increased vessel permeability, leading to subsequently enhanced FIGURE 1 | Role of the extracellular matrix in driving progression through stages of the metastatic cascade.…”
Section: Invasion and Intravasationmentioning
confidence: 99%